0
$\begingroup$

let $a_n = \frac {(1+(-1)^n)}{2^n} + \frac {(1 +(-1)^{n-1})}{3^n}$. then find the the radius of convergence of the following power series $\sum_{n=1} ^{\infty}a_nx^n$ about $ x =0$?

My attempts :by Cauchy–Hadamard theorem the radius of convergence will be 1

$\endgroup$
  • 1
    $\begingroup$ The series converges for $|x|<2$. $\endgroup$ – Mark Viola May 7 '18 at 16:39
3
$\begingroup$

You can write that $$ a_{2n}=\frac{1}{2^{n-1}} \text{and } a_{2n+1}=\frac{2}{3^n}$$ You can see that $$ \frac{a_{2n+2}}{a_{2n}}=\frac{1}{2} \text{ and }\frac{a_{2n+3}}{a_{2n+1}}=\frac{1}{3} $$ Hence the radius of convergence is equal to min$(R_1,R_2)=2$.

$\endgroup$
  • $\begingroup$ thanks a lots @Atmos $\endgroup$ – jasmine May 8 '18 at 2:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.